2021
DOI: 10.2188/jea.je20190347
|View full text |Cite
|
Sign up to set email alerts
|

Population Attributable Fractions of Modifiable Risk Factors for Nonsyndromic Orofacial Clefts: A Prospective Cohort Study From the Japan Environment and Children’s Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…This high volume of research should have provided a clear indication of the association between maternal smoking and CL/P, but the poor quality of studies overall has compromised the reliability of the reported findings. Only three studies out of the 45 included in this review were judged to be of good quality (Grewal et al, 2008;Raut et al, 2019;Sato et al, 2020;). The most common reason for poor quality within the studies was a failure to adjust for recognized confounding factors, placing the analyses at high risk of bias.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This high volume of research should have provided a clear indication of the association between maternal smoking and CL/P, but the poor quality of studies overall has compromised the reliability of the reported findings. Only three studies out of the 45 included in this review were judged to be of good quality (Grewal et al, 2008;Raut et al, 2019;Sato et al, 2020;). The most common reason for poor quality within the studies was a failure to adjust for recognized confounding factors, placing the analyses at high risk of bias.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This high volume of research should have provided a clear indication of the association between maternal smoking and CL/P, but the poor quality of studies overall has compromised the validity of the reported findings. Only three studies out of the 45 included in this review were judged to be of good quality (Grewal et al, 2008; Raut et al, 2019; Sato et al, 2020). The most common reason for poor quality within the studies was a failure to adjust for recognized confounding factors, placing the analyses at high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Brazil found elevated but nonsignificant risk associated with alcohol consumption at the highest frequency measured (OR = 1.55, 95% CI: 0.56, 4.26). Another recent study in Japan also observed no relationship between maternal drinking and OFC by two metrics: the mother quit drinking after pregnancy (OR = 0.87, 95% CI 0.63, 1.22) versus current drinker during pregnancy (OR = 0.71, 95% CI: 0.22, 2.27; Sato et al, 2020). Meta‐analysis by Yin et al similarly found no relationship between any drinking and CL/P (OR = 1.00, 95% CI: 0.87, 1.15) or CPO (OR = 1.02, 95% CI: 0.92, 1.14; Yin et al, 2019).…”
Section: Behavioral Risk Factors For Ofcsmentioning
confidence: 92%
“…Honein et al found that up to 6.1% of OFC cases in the United States could be prevented by ceasing maternal active smoking in the periconceptual period of pregnancy (Honein et al, 2014). A recent prospective case–control study on a Japanese population indicated that the PAF of CL/P due to maternal active smoking is 9.9%, and 10.8% for passive smoking (Sato et al, 2020).…”
Section: Behavioral Risk Factors For Ofcsmentioning
confidence: 99%